Do sex ratio and development differ in sexually size‐dimorphic shiny cowbirds (Molothrus bonariensis) parasitizing smaller and larger hosts?. (12th July 2013) - Tuero, Diego T.; Fiorini, Vanina D.; Mahler, Bettina; Reboreda, Juan C.
Abstract : Two possible patterns of bias in primary sex ratio have been proposed for size‐dimorphic brood parasites that do not evict host chicks: (1) larger males should be laid at greater frequency in hosts larger than the parasite because they compete better (increasing their survival) than females with large host nest‐mates, and (2) more costly males (i.e. the larger sex) should be laid at greater frequency in hosts smaller than the parasite because, in these hosts, parasite nestlings are provisioned at a higher rate and grow faster than in larger hosts. We tested these hypotheses in two hosts of the sexually size‐dimorphic shiny cowbird, Molothrus bonariensis, one smaller (house wren, Troglodytes aedon ) and one larger (chalk‐browed mockingbird, Mimus saturninus ) than the parasite. We measured: (1) sex ratio at laying; (2) development of sexual differences in body mass during the nestling stage; and (3) chick survival and sex ratio of chicks before fledging. In both hosts, we found sexual differences in body mass of nestlings from 7 days of age onwards, although we did not find a bias in the sex ratio of eggs laid and chicks fledged. The results of the present study do not support the hypothesis that shiny cowbird females benefit from biasing the primary sex ratio depending on the size of the hosts they parasitize. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 442–448.